'My wood isn't one of those dark and scary ones': children's experience and knowledge of woodland in the English rural landscape. (4th July 2019) - Lisewski-Hobson, Vivyan; Watkins, Charles
ABSTRACT: Recent studies of children have argued that children are suffering from a deficiency in nature experience. Some argue that a lack of experience leads to poor affective relations which for wooded environments may be manifested as fear. This study investigates a geographical knowledge gap in understanding children's relationships with woodland. This interactive qualitative study included 21 junior age children living in a rural setting in Derbyshire, England, UK. Most were found to visit local woodlands regularly, though unsupervised visits were usually limited to woods adjacent to housing. The children demonstrated good levels of practical knowledge though explicit knowledge, such as tree names, was generally poor. The majority of children had positive attitudes towards woodland, especially those with the greatest experience. Adventure, calm and freedom were identified as major themes. Fear was widespread but rarely dominated and was often associated with exhilaration linked to cultural imaginaries such as computer games and films.